DINAMIKA HUKUM ISLAM BERDASARKAN MASLAHAH (ISTITHA’AH BAGI JAMAAH HAJI) - Muslihuddin, Gusti; Jalaluddin, Jalaluddin; Zaki Mubarak, Muhammad (Program Studi Hukum Keluarga Islam STAI Al-Falah Banjarbaru, 2024)
AbstractThis research will examine the principles of benefit in the issue of limiting the age of marriage and istitha'ah for Hajj pilgrims, with various legal, medical and social approaches to achieve sharia goals.Normative legal research methods. Multidisciplinary approach with other scientific disciplines. Techniques for collecting library legal materials are presented qualitatively.The aim of limiting the age for marriage is to ensure that individuals who are getting married have maturity in thinking, emotional maturity and physical strength. Marriage dispensation is the realm of judge's ijtihad in giving decisions that are worth maslahah. Overcoming early marriage through counseling, involving religious figures. Education must pay attention to character building and a culture of shame in interacting with the opposite sex.Istitha'ah indicators for the implementation of the Hajj pilgrimage in Indonesia are contained in Law no. 08 of 2019. Hajj quota, health and financial conditions influence the istitha'ah of Hajj pilgrims. Road safety, mahram rules and the possibility of getting there are no longer benchmarks. Hajj quotas and hajj waiting lists never existed in classical times, while the health and cost aspects are still the same, only the size and management are carried out by the government.In conclusion, classical Islamic studies do not limit the age of marriage, and stability is not a criterion for marriage readiness. Contemporary studies, limiting the age of marriage and istitha'ah can be carried out using mashlahah and maqashid asy-syariah instruments. Multidisciplinary studies must be carried out.Keywords: Early marriage, Hajj, Contemporary. Abstrak Penelitian ini akan mengkaji bagaimana prinsip kemaslahatan dalam masalah pembatasan usia nikah dan istitha'ah bagi jamaah haji, dengan berbagai pendekatan hukum, medis, dan sosial untuk mencapai tujuan syariah.Metode penelitian hukum normatif. Pendekatan multidisiplin dengan disiplin ilmu lainnya. Teknik pengumpulan bahan hukum kepustakaan disajikan secara kualitatif.Pembatasan usia untuk melangsungkan perkawinan tujuannya agar individu yang akan menikah sudah memiliki kematangan berpikir, kedewasaan emosional, dan kekuatan fisik. Dispensasi pernikahan merupakan ranah ijtihad hakim dalam memberikan putusan yang bernilai maslahah. Penanggulangan pernikahan dini dengan penyuluhan, melibatkan tokoh-tokoh agama. Pendidikan harus diperhatikan tentang pembangunan karakter dan budaya malu dalam pergaulan dengan lawan jenis.Indikator istitha’ah pada pelaksanaan ibadah haji di Indonesia termuat dalam UU No. 08 tahun 2019. Kouta haji, kesehatan dan keadaan finansial berpengaruh pada istitha’ah jamaah haji. Keamanan jalan, aturan mahram dan kemungkinan sampai tidak lagi menjadi tolak ukur. Kouta haji dan daftar tunggu haji belum pernah ada di zaman klasik, sedangkan aspek kesehatan dan biaya masih sama, hanya saja besaran dan manajemennya oleh pemerintah.Kesimpulan, kajian Islam klasik tidak membatasi usia pernikahan, dan kemapanan bukan kriteria kesiapan pernikahan. Kajian kontemporer, pembatasan usia pernikahan dan istitha’ah dapat dilakukan dengan instrument mashlahah dan maqashid asy-syariah. Kajian multidisiplin harus dilakukan.Kata Kunci: Pernikahan dini, Haji, Kontemporer